Implementation of The Concept of Humanistic Education in The Qur'an Perspective of Surat Al-Isra’ : 70 - Tsania Rosyidah Hasna; Rahmat Arofah Hari Cahyadi (Studia Religia : Jurnal Pemikiran dan Pendidikan Islam, 2020)
Realities that occur related to the role of the environment in shaping the learner's personality are largely incompatible with the concept of humanistic education. The implications of the negative environmental role have an impact on moral degradation. Moral degradation of students includes free sex, crime, loss of courtesy towards educators, and loss of moral values in students. There are two external and internal factors in the emergence of moral degradation in students. The existence of humanistic education as a fortress to prevent moral degradation. The focus of the study is on the concept of humanism education, the influence of humanism education on students' social interactions, humanism education in the perspective of Al-Isra 'Verse 70, and the implementation of humanism education according to Al-Isra' Verse 70 in the education of learners. This type of research is in the form of library research. With content analysis approach. The researchers' findings cover the activities carried out by students in the learning process that follows the flow and norm procedures that are the rules in the relevant educational institution. The activity can be in the form of social interactions that lead to the formation of character and the development of abilities and talents possessed by students formed on the basis of Pancasila and religious values. Keywords: Concept, Education, Humanistic Education